Building enterprises industrial structure's optimisation / Statybos įmonių gamybinės struktūros optimizavimas - Ginevičius, R.; Čirba, S. (Journal of Civil Engineering and Management, 1996)
Building enterprises industrial programme which is muolded by the way of competition, could hesitate in rather wide limits: in its quantity and expenditure of labour structure. It is possible to expect high results of activity only then, if building enterprises would be able to adjust properly near changeable environment. You could do this only if you reorganisate its industrial structure. Two sides could be responsible for this formation-constant and changeable. The first side must ensure enterprises potential, the high works quantity and paces. The second one must compensate industrial programme scale and structures hesitation. If you want to find awarded parts quantity you must solve optimisation problem it means to define what volume of works during the analysing period must do its “nucleus” units that the recieved profit would be the greatest one.Article in Lithuanian.First Published Online: 26 Jul 2012